Determining cutting force coefficients from instantaneous cutting forces in ball end milling. (2016) - Dikshit, Mithilesh K.; Puri, Asit Baran; Maity, Atanu; Banarjee, Amit Jyoti
The precise prediction of cutting forces helps in improving the machining performances. This involves the modelling of cutting force components in tangential, radial and axial directions and determination of respective specific cutting force coefficients. In the present work, an improved method of identification of specific cutting force coefficient is proposed for ball end milling cutter using semi-mechanistic force model. The cutter is discretised into a finite number of axial discs along the axis of the cutter. Using the geometry of ball end milling cutter, true uncut chip thickness is modelled based on the trochoidal trajectory of a cutting edge element. Specific cutting force coefficients have been determined through inverse method. Also, a fourth order polynomial curve fitting method has been employed to establish a mathematical relationship between the said coefficients and axial depth of cuts. Several experiments have been carried out at different feed rate and axial depth of cut to determine the specific cutting force coefficients based on the proposed identification method. Validation results show good agreement between predicted and experimental results. Compared to conventional identification model, the specific force coefficient identification process discussed in the present paper is fast, convenient and accurate.